2016
DOI: 10.1111/ejn.13158
|View full text |Cite
|
Sign up to set email alerts
|

Orexin gene transfer into the amygdala suppresses both spontaneous and emotion‐induced cataplexy in orexin‐knockout mice

Abstract: Narcolepsy is a chronic sleep disorder linked to the loss of orexin-producing neurons in the hypothalamus. Cataplexy, a sudden loss of muscle tone during waking, is an important distinguishing symptom of narcolepsy and it is often triggered by strong emotions. The neural circuit underlying cataplexy attacks is not known, but is likely to involve the amygdala, a region implicated in regulating emotions. In mice models of narcolepsy, transfer of the orexin gene into surrogate neurons has been successful in ameli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…However, mice with such restoration have demonstrated frequent CLEs (8) in conditions with or without chocolate feeding (Table S5). Because those results suggest that endogenous orexin release in the amygdala cannot alone prevent CLEs, suppressing cataplexy in orexin-deficient mice with the ectopic overexpression of orexin peptides in the amygdala is clinically relevant but perhaps not physiological (37). Similar to our current findings, results of other studies, including our own, have shown that orexin neurons regulate the amygdala indirectly via LC noradrenergic neurons as part of modulating fear learning (38,39).…”
Section: Chemogenetic Manipulations Of Amygdala Activity Bidirectionallysupporting
confidence: 88%
“…However, mice with such restoration have demonstrated frequent CLEs (8) in conditions with or without chocolate feeding (Table S5). Because those results suggest that endogenous orexin release in the amygdala cannot alone prevent CLEs, suppressing cataplexy in orexin-deficient mice with the ectopic overexpression of orexin peptides in the amygdala is clinically relevant but perhaps not physiological (37). Similar to our current findings, results of other studies, including our own, have shown that orexin neurons regulate the amygdala indirectly via LC noradrenergic neurons as part of modulating fear learning (38,39).…”
Section: Chemogenetic Manipulations Of Amygdala Activity Bidirectionallysupporting
confidence: 88%
“…To synchronize the timestamps of the Ca 2+ imaging with the EEG/EMG, a TTL signal was sent from the nVoke interface console into the Doric console. After 30 min of undisturbed recording, the mouse was exposed to milk (whole milk, 2 mL) for 30 min and coyote urine (1 mL, www.predatorpee.com, Bangor, ME) for 30 min between 5:30 P.M. and 7:00 P.M. (Liu et al, 2016).…”
Section: Miniature Microscopy Ca 2+ Transients Imagingmentioning
confidence: 99%
“…Cataplexy is a distinguishing symptom of narcolepsy. In animal models, cataplexy can be experimentally elicited by deletion of the orexin gene (orexin‐KO mice), leaving the neurons intact. In these mice, orexin gene transfer to neurons in the lateral hypothalamus using replication‐defective herpes simplex virus 1 (HSV‐1) reduces cataplexy and restores normal sleep‐wake behavior during the 4‐day lifetime of the vector .…”
Section: Gene Therapymentioning
confidence: 99%